2003
DOI: 10.1111/j.1749-6632.2003.tb07539.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Vitamin D3 Attenuated Oxidative Injuries in the Locus Coeruleus of Rat Brain

Abstract: Iron-induced oxidative injuries in locus coeruleus (LC), a major source of noradrenergic projections in the central nervous system (CNS), were investigated in chloral-hydrate anesthetized rats. Local infusion of iron dose-dependently elevated lipid peroxidation of iron-infused LC seven days after infusion. At the same time, norepinephrine content in the hippocampus ipsilateral to the iron-infused LC was decreased in a concentration-dependent manner. Our immunostaining study demonstrated reduced tyrosine hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 35 publications
0
40
0
1
Order By: Relevance
“…In previous studies, it has been demonstrated that vitamin D3 is a modulator of brain development , a regulator of VDR and NGF (Neveu et al, 1994;Cornet et al, 1998;Veenstra et al, 1998;Baas et al, 2000;Taniura et al, 2006) and it is able to reverse experimental autoimmune encephalomyelitis (Spach et al, 2004). Moreover, vitamin D3 is considered an antioxidant that reduced oxidative injuries in the brain (Chen et al, 2003;Lin et al, 2005) or a potential and represent the mean 6 s.e.m of three independent experiments performed in duplicate. Vitamin D3 induces PCNA and cyclin D decrease and Bcl2 increase.…”
Section: Discussionmentioning
confidence: 97%
“…In previous studies, it has been demonstrated that vitamin D3 is a modulator of brain development , a regulator of VDR and NGF (Neveu et al, 1994;Cornet et al, 1998;Veenstra et al, 1998;Baas et al, 2000;Taniura et al, 2006) and it is able to reverse experimental autoimmune encephalomyelitis (Spach et al, 2004). Moreover, vitamin D3 is considered an antioxidant that reduced oxidative injuries in the brain (Chen et al, 2003;Lin et al, 2005) or a potential and represent the mean 6 s.e.m of three independent experiments performed in duplicate. Vitamin D3 induces PCNA and cyclin D decrease and Bcl2 increase.…”
Section: Discussionmentioning
confidence: 97%
“…Decrease in intracellular glutathione content may be related to the primary event in Parkinson's disease, while calcitriol's antioxidant actions have been shown to enhance intracellular glutathione concentration and to protect against reactive oxygen species in the central nervous system (Garcion et al 2002). Upregulation of glia-derived neurotrophic factors (GDNFs) with consequent antioxidative activity has been proposed responsible for vitamin D 3 -induced neuronprotection (Chen et al 2003). Neurosteroids are a group of steroid hormones synthesized by the brain in the presence of steroidogenic enzymes.…”
Section: Vitamin D: Neuroprotectionmentioning
confidence: 99%
“…The accumulation of ferric iron in cells leads to ROS formation via the Fenton reaction, causing DNA strand breaks [47]. In the locus ceruleus of rat brains, pretreatment with calcitriol before iron-mediated cellular injury resulted in lower levels of cytochrome c and less lipid peroxidation [34]. Calcitriol has also been shown to protect neuronal cells from injury due to iron-related oxidation.…”
Section: Vitamin D and The Injured Brainmentioning
confidence: 99%
“…GDNF has been shown to be an important neuroprotective factor, and increased levels of GDNF have been demonstrated after treatment with calcitriol in models of oxidative brain injury [34] and autoimmune encephalitis [35]. Treating neuronal cells with calcitriol also increases levels of c-Ret mRNA, a GDNF receptor [36].…”
Section: Vitamin D and The Injured Brainmentioning
confidence: 99%